Effect of Biologics on Cardiovascular Inflammation: Mechanistic Insights and Risk Reduction - Fragoulis GE; Soulaidopoulos S; Sfikakis PP; Dimitroulas T; Kitas GD (Dove Medical Press, 2021)
George E Fragoulis,1,* Stergios Soulaidopoulos,2,* Petros P Sfikakis,1 Theodoros Dimitroulas,3 George D Kitas4,5 1Rheumatology Unit, Joint Rheumatology Program, Medical School, First Department of Propaedeutic Internal Medicine, National and Kapodistrian University of Athens, “Laiko” General Hospital, Athens, 115 27, Greece; 2First Department of Cardiology, National and Kapodistrian University of Athens, Hippokration General Hospital, Athens, 115 27, Greece; 3Fourth Department of Internal Medicine, Hippokration Hospital, School of Medicine, Aristotle University of Thessaloniki, Thessaloniki, 546 41, Greece; 4Department of Rheumatology, Russells Hall Hospital, Dudley Group NHS FT, Dudley, DY1 2HQ, UK; 5Arthritis Research UK Epidemiology Unit, University of Manchester, Manchester, M13 9PT, UK*These authors contributed equally to this workCorrespondence: Stergios SoulaidopoulosFirst Department of Cardiology, National and Kapodistrian University of Athens, 114 Vasilissis Sofias av., Athens, 11527, GreeceTel +306932528561Fax +302132088676Email soulaidopoulos@hotmail.comAbstract: It is increasingly recognized that atherosclerosis and consequently cardiovascular disease (CVD) are closely linked with inflammatory processes. The latter is in the center of the pathogenic mechanism underlying autoimmune rheumatic diseases (ARD). It follows then, that optimal control of inflammation in ARDs may lead to a decrease of the accompanied CVD risk. Major trials (eg, CANTOS, CIRT), aimed at examining the possible benefits of immunomodulatory treatments in CVD, demonstrated conflicting results. On the other hand, substantial evidence is accumulating about the possible beneficial effects of biologic disease modifying antirheumatic drugs (bDMARDs) in patients with ARDs, particularly those with rheumatoid arthritis (RA). It seems that bDMARDs (some more than others) alter the lipid profile in RA patients but do not adversely affect, in most cases, the TC/HDL ratio. Favorable effects are noted for arterial stiffness and endothelial function. This is reflected in the lower risk for CVD events, seen in observational studies of RA patients treated with bDMARDs. It should be stressed that more data exist for the TNF-inhibitors than for other bDMARDs, such as tocilizumab, abatacept and rituximab. As regards the spondyloarthropathies (SpA), data are less robust. For TNF-inhibitors, effects appear to be on par with those seen in RA but no conclusions can be drawn for newer biologic drugs used in SpA (eg, IL-17 blockers). Finally, there is accumulating evidence for a beneficial effect of immunosuppressive treatment in cardiac inflammation and function in several ARDs. Introduction of newer therapeutic options in clinical practice seem to have a positive impact on CVD in the setting of ARD. This is probably due to better control of inflammation, but direct improvement in vascular pathology is also a valid hypothesis. Most data are derived from observational studies and, therefore, randomized controlled trials are needed to assess the possible favorable effect of bDMARDs on CVD outcomes.Keywords: atherosclerosis, cardiovascular disease, biologic agents, interleukins, inflammatory disorders